TEACHER MEDIATION OF EVERYDAY MATHEMATICS IN URBAN AND RURAL KINDERGARTENS - Nurfaida; Sitti Nurhidayah Ilyas; Hajerah (CV. TOTUS TUUS, 2026)
Early mathematics often appears in routines and play, but the pedagogical processes by which teachers make these experiences mathematically explicit remain underdescribed, particularly across contrasting resource contexts. This qualitative multi-site case study examined how teachers in one urban kindergarten in Makassar City and one rural kindergarten in Gowa Regency, South Sulawesi, integrated mathematical activities into the daily experiences of children aged 5–6 years. Five adult informants—three teachers and two principals—participated; children were observed as classroom participants, but individual learning outcomes were not measured. Data from non-participant observation, semi-structured interviews, photographs, videos, field notes, and lesson documents were analyzed through inductive first-cycle coding followed by framework-guided mapping to six Realistic Mathematics Education principles and Bishop’s six mathematical activities. Across the two cases, reported practices were analytically consistent with reality, activity, levels, intertwinement, interactivity, and guidance. Counting, measuring, locating, designing, playing, and explaining were identified in routine classroom activity. The urban site relied more on structured media and teacher-directed routines, whereas the rural site drew more on natural materials, movement, and environmental exploration. These patterns suggest—without establishing causality or learning effectiveness—that different resource ecologies can support comparable forms of contextual mathematical mediation. The study contributes a non-causal analytic framework linking contextual resources, teacher mediation, and visible mathematical activity. Transferability is limited by the two-site design, incomplete child-level reporting, and the absence of measured learning gains. Future research should use larger samples, detailed video coding, multiple analysts, and longitudinal or design-based methods.